Chemically Modified Polyvinyl Butyral Polymer Membrane as a Gel Electrolyte for Lithium Ion Battery Applications. Issue 1 (26th November 2018) - Xu, Ziqiang; Li, Wenlei; Chen, Zhi; Wang, Dongxia; Feng, Tingting; Potapenko, Hanna; Wu, Mengqiang
Abstract: A novel porous membrane of chemically modified polyvinyl butyral (mPVB), with improved thermal properties and chemical stability for lithium ion battery applications, is successfully synthesized by utilizing the chain extension reaction of the OH units from PVB. The porous mPVB membranes are obtained via the tape casting and phase inversion method. The corresponding gel polymer electrolyte (GPE) is achieved by immersing the as‐prepared membranes in the liquid electrolyte. The electrochemical performances of the GPE show that the mPVB membranes have the features of good uniformity, high porosity (≈ 90%), great thermal stability, and high mechanical strength. Moreover, the GPE exhibits good chemical stability, a wide electrochemical window, as well as high ionic conductivity (≈ 1.21 × 10 −3  S cm −1 ). A test of a Li/GPE/LiFePO4 battery cell shows a capacity of 147.7 mAh g −1 and excellent cycling stability, demonstrating the great potential of the mPVB‐based GPE for lithium ion battery applications. Abstract : Porous modified polyvinyl butyral (mPVB) membranes are successfully synthesized by using the tape casting and phase inversion method for lithium ion battery applications. The proposed membranes with improved thermal properties, good uniformity, high porosity (≈90%), high mechanical strength, and chemical stability based on this easy preparation method indicate their good engineering potential.